REMOTE SENSING AND GIS APPROACHES TO A QUALITATIVE ASSESSMENT OF SOIL EROSION RISK IN SERANG WATERSHED, KULONPROGO, INDONESIA - Nursida Arif; Projo Danoedoro; Hartono Hartono (Geoplanning: Journal of Geomatics and Planning, 2017)
This research aims to determine the risk of soil erosion qualitatively by integrating remote sensing with the geographic information system. Factors that contributed to the occurrence of erosion in the area of study were analyzed using the method of the variation of combined input data of the factors controlling erosion (soil, climate, topography, vegetation, and humans). The input data were quantitative data changed into qualitative data that were obtained from field data and extracted from remote sensing imagery, i.e. SPOT 5. A number of parameters were calculated using the RUSLE model equation. The model was validated by observing the qualitative erosion indicators in the field (pedestal, tree root exposure, armor layers, rill erosion, and gully erosion) by observing slope steepness in each sample area. The area of study was Serang watershed located in Kulon Progo Regency, Yogyakarta. It is one of the critically potential watersheds viewed from the landform and land use. The results of various combinations generated the highest of accuracy by 90.57 % with extremely erosion dominating the area of study. The factors with the highest contribution to erosion in Serang Watershed were slope length and steepness (LS) and erodibility (K).